ن م راشد اور مجید امجد کے ہاں جدید انسان کی پیش کشPresentation of Modern man by Noon Meem Rashid and Majid Amjad (Al-Qamar, 2020)
Noon Meem Rashid and Majeed Amjad are considered among the modern poets of Urdu. It is because they have different forms of concept of modern man and all his problems. Especially, the aspects on the chaotic side of the inner self and personal detachments are presented by these two poets at the collective level with individuality. Thus, their concept of man becomes a representative of locality and global scenario. In this context, some intellectual similarities and differences can also be seen between these poets. This has been discussed in the current article, so that the different forms of human beings with the evolutionary forms of both the poets become clear.
Keywords: Personal Detachments; Modern Poets; Inner Self; personal Detachments